Poly(Lactide-co-Glycolide) Nanocapsules Containing Benzocaine: Influence of the Composition of the Oily Nucleus on Physico-Chemical Properties and Anesthetic Activity - Silva de Melo, Nathalie Ferreira [UNESP]; Grillo, Renato [UNESP]; Guilherme, Viviane Aparecida; de Araujo, Daniele Ribeiro; de Paula, Eneida; Rosa, Andre Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Springer/plenum Publishers, 2011)
The aim of this work was to investigate the influence of the oily nucleus composition on physico-chemical properties and anesthetic activity of poly (lactide-co-glycolide) nanocapsules with benzocaine.Nanocapsules containing benzocaine were prepared with three different oily nucleus composition and characterized by mean diameter, polydispersivity, zeta potential, pH and stability were investigated as a function of time. In vitro release kinetics were performed in a system with two compartments separated by a cellulose membrane. Intensity and duration of analgesia were evaluated in rats by sciatic nerve blockade.The greatest stability, slower release profile and improvement in the local anesthetic activity of BZC were obtained with the formulation using USP mineral oil as component.Results from our study provide useful perspectives on selection of the primary materials needed to produce suspensions of polymeric nanocapsules able to act as carriers of BZC, with potential future application in the treatment of pain.
Keywords: benzocaine; local anesthetic; nanocapsule; oily nucleus; PLGA